CRITICIZING INCOHERENCES IN THE SHARIA TRANSACTION PARADIGM: THE CASE OF SHARIA FINANCIAL REPORTING FRAMEWORK IN INDONESIA - Birton, M. Nur A.; Sholihin, Mahfud (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims at first investigating and criticizing the use of “sharia transaction paradigm” and showing the internal incoherences as preamble, foundation, and bond of goals and concepts contained in the body of Sharia Framework for Preparation and Presentation of Financial Statements in Indonesia; second, using Tahwidi methodological worldview as the reflection to show external incoherences due to the extensive and holistic Islam goals.This research used a qualitative approach to examine various logical mistakes and incoherences when investigating “sharia transaction paradigm” concepts and/or proposition in the script of sharia transaction preamble of Indonesia’s Sharia Framework for Preparation and Presentation of Financial Statements. Mistakes and incoherences analysis used the logical induction and deduction pathways; while Tawhidi methodological worldview was used to show the “sharia transaction paradigm” incoherences with the other parts of sharia entity operation reporting conceptual framework and more comprehensive sharia goals.This article found four “sharia transaction paradigm” internal incoherences as sharia preamble (foundation) in Sharia Framework for Preparation and Presentation of Financial Statements. Through Tahwidi methodological worldview, “sharia transaction paradigm” failed to coherently bond a number of Sharia Framework elements as one Islamic accounting subsystem and its environments covering the material, morale, and spiritual aspects.This study is a recent work reviewing and criticizing the use of sharia transactions, especially sharia transaction paradigm to show the Indonesia’s Sharia Framework for Preparation and Presentation of Financial Statements. Tahwidi methodological worldview has the chance to substitute sharia transactions and as the foundation to build a new Sharia Framework.